SEKOLAH PENGASUHAN CERDAS: PENGUATAN ORANGTUA DALAM PENGASUHAN HOLISTIK DAN TRANSFORMATIF - Grahani, Firsty Oktaria; Agustini, Ardianti; Putrih, Nabilla Maydina; Khosiyah, Mitsliatun (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2025)
In the modern era, characterised by technological advances, complex social dynamics, and increasing economic and psychological pressures, child-rearing practices face increasingly diverse challenges. Parents now play dual roles as breadwinners and primary educators, which has led to a decline in the quality of interaction and consistency in parenting styles. This phenomenon has given rise to various parenting issues such as permissive, authoritarian, and even neglectful parenting styles. Various studies show common problems in parenting today, including: inconsistency in parental attitudes, lack of understanding of child development, use of violence as discipline, weak supervision in the use of gadgets, minimal quality time with children, limited access to parenting education, and gender inequality in parenting. The problems that arise are a decline in the quality of parent-child interaction; inconsistency in parenting styles; a lack of parental knowledge about child development; the use of violence as a method of discipline in parenting; weak digital supervision and guidance; limited access to parenting education; and gender role inequality between fathers and mothers. The solutions and desired outcomes are to provide parents with additional knowledge and insights into comprehensive parenting at every stage of their child's development through presentations, case studies, and discussions; to provide parents with an understanding of effective and communicative parenting through case studies and sharing sessions. The methods used in the parent strengthening programme in holistic and transformative parenting are baseline measurements to identify the parenting practices used so far so that appropriate and needs-based psychoeducation can be designed (pre-post test); developing an empowerment programme to be implemented; providing parents with an understanding of holistic and transformative parenting and effective communication with children from early childhood to adulthood in the form of material presentation, video screening and discussion; Sharing sessions on each parent's child-rearing experiences to enrich the knowledge of each parent and provide assistance in the form of counselling related to obstacles or problems or even progress encountered during the implementation of parenting. The results showed an increase in understanding among parents and SOTH managers, particularly in terms of parenting, as evidenced by the pre- and post-test results. The provision of various psychoeducation methods through role-play, sharing sessions, and case studies made it easier for parents and managers to understand the material presented. The method of sharing parenting experiences made psychoeducation more applicable, thereby improving inappropriate parenting patterns that had been practised at home.